Detection of GFAP and D‐Dimer in a Point‐of‐Care Test for Large Vessel Occlusion Ischemic Stroke - Edoardo Gaude; Danielle Murphy; Jakob V.E. Gerstl; Ari D. Kappel; Adam A. Dmytriw; Noah L.A. Nawabi; Saef Izzy; Rodolfo E. Alcedo Guardia; Juan C. Vicenty‐Padilla; Toby Gropen; Nirav J. Patel; David S. Liebeskind; et al. (Stroke: Vascular and Interventional Neurology)
Background The blood biomarkers GFAP (glial fibrillary acidic protein)  and D‐dimer have been shown to accurately diagnose large vessel occlusion ischemic stroke. The Upfront DX LVOne is a novel lateral flow‐based point‐of‐care test used for the detection of GFAP and D‐dimer. This study sought to (1) assess the performance of LVOne against commercially available point‐of‐care test platforms, which independently detect GFAP and D‐dimer (Abbott iSTAT TBI Plasma and LumiraDx D‐dimer), and to (2) assess the diagnostic performance of LVOne in large vessel occlusion detection. Methods Manufacturer‐reported detection thresholds of the LVOne test for GFAP and D‐dimer (213 pg/mL and 600 ng/mL, respectively) were compared against commercial hospital‐based point‐of‐care test platforms using 20 randomly selected plasma samples for each biomarker. D‐dimer correlation between LVOne and LumiraDx was assessed using Spearman's Rank correlation coefficient; GFAP correlation between LVOne and the Abbott iSTAT TBI results were assessed using point biserial correlation. Diagnostic performance of the LVOne point‐of‐care test in conjunction with clinical assessment for detection of large vessel occlusion in plasma samples from 210 patients with suspected stroke was validated. Results There was a strong positive correlation (Rho = 0.86, P<0.001) between the qualitative scoring of the lateral flow test and serum GFAP concentrations. Similarly, there was a significant positive correlation between the D‐dimer quantification and LVOne semiquantitative measurements (Rho = 0.90; P<0.0001). In our cohort of 210 patients with suspected stroke, the LVOne test in conjunction with clinical assessment had a sensitivity of 75% (95% CI, 51%–91%), a specificity of 92% (95% CI, 87%–95%), a positive predictive value of 48% (95% CI, 30%–67%), and a negative predictive value of 97% (95% CI, 94%–99%) for detection of large vessel occlusion. Conclusion Our results validate detection thresholds for the LVOne test in a representative cohort of plasma samples of patients with suspected stroke. Further studies are required to demonstrate the efficacy, safety, and diagnostic performance of LVOne in capillary blood during emergency care/clinical triage.